Total Quality Management Practices In Malaysian Small and Medium Enterprises - Hakim, Razak; Fatimah, Mahmud; Fazeeda, Mohamad (ESB Business School, 2016)
The purpose of this paper is to examine the status of TQM implementation within Malaysian SMEs. Specifically, this paper has two research objectives, firstly, to analyze the extent of quality management practices based on eight TQM principles in both ISO 9000 certified and noncertified Malaysian SMEs and secondly, to determine the quality techniques and tools being practiced in local SMEs. The sample of this study consists of 27 respondents from the selected companies taken from SME Corporation Malaysia database. The data was collected using survey questionnaire and analyzed with the application of SPSS 22.0 computer programme. The findings state that SMEs are actively practicing the quality techniques and tools. The results indicate that internal audits were being practiced in all of the responded companies and 63 percent were utilizing problem solving methodology. In addition, findings show that SMEs are still at the infancy stage in adopting TQM based on eight key principles. The mean values ranged from „moderate‟ to „high‟ in term of extent of practices. Factual Approach to Decision Making‟ and is rated as the most practiced principle by the SMEs with the mean value of 4.39. Additionally, the findings indicated that „Management Leadership‟ is placed among the most adopted principle as well with the mean value of 4.33. Moreover, the t-test results suggest that there is no significant difference between ISO 9000-certified and ISO 9000-uncertified SMEs since all the factors presented p-value less than 0.05. In terms of practical implication, this research finding is expected to provide foundations on developing appropriate TQM framework within Malaysian SMEs in the future to improve their business performance. However, the limitations of this research are that the data obtained is based on the perceptions of managers and the diversity of the sample companies which came from various sectors.